A psychometric evaluation of the Vietnamese version of the Affiliate Stigma Scale - Thi Loan Khanh; Phuong Anh Hoang; Hop Tan Nguyen; Anh T.L Mai (Revista de Enfermagem Referência)
Background: The Affiliate Stigma Scale (ASS) is the most used instrument to assess affiliate stigma in caregivers with different mental health issues. However, there has not been a Vietnamese version of this scale with clear psychometric properties.